A duplex DNA–gold nanoparticle probe composed as a colorimetric biosensor for sequence-specific DNA-binding proteins. Issue 6 (23rd February 2016) - Ahn, Junho; Choi, Yeonweon; Lee, Ae-Ree; Lee, Joon-Hwa; Jung, Jong Hwa
Abstract : The SPL-12-mediated change of Au aggregation via duplex DNA–SPL-12 interactions could be utilized for colorimetric sensing of SPL-12 using duplex DNA–Au. Abstract : Using duplex DNA–AuNP aggregates, a sequence-specific DNA-binding protein, SQUAMOSA Promoter-binding-Like protein 12 (SPL-12), was directly determined by SPL-12-duplex DNA interaction-based colorimetric actions of DNA–Au assemblies. In order to prepare duplex DNA–Au aggregates, thiol-modified DNA 1 and DNA 2 were attached onto the surface of AuNPs, respectively, by the salt-aging method and then the DNA-attached AuNPs were mixed. Duplex-DNA–Au aggregates having the average size of 160 nm diameter and the maximum absorption at 529 nm were able to recognize SPL-12 and reached the equivalent state by the addition of ∼30 equivalents of SPL-12 accompanying a color change from red to blue with a red shift of the maximum absorption at 570 nm. As a result, the aggregation size grew to about 247 nm. Also, at higher temperatures of the mixture of duplex-DNA–Au aggregate solution and SPL-12, the equivalent state was reached rapidly. On the contrary, in the control experiment using Bovine Serum Albumin (BSA), no absorption band shift of duplex-DNA–Au aggregates was observed.